Pressure-induced isostructural electronic topological transitions in 2H-MoTe2: x-ray diffraction and first-principles study. (6th November 2020) - Bera, Achintya; Singh, Anjali; Gupta, Satyendra Nath; Glazyrin, K; Muthu, D V S; Waghmare, U V; Sood, A K
Abstract: Synchrotron x-ray diffraction measurements on powder 2H-MoTe2 ( P 63 / mmc ) up to ∼46 GPa have been performed along with first-principles based density functional theoretical analysis to probe the isostructural transition in low pressure regime and two electronic topological transitions (ETT) of Lifshitz-type in high pressure regime. The low pressure isostructural transition at ∼7 GPa is associated with the lattice parameter ratio c / a anomaly and the change in the compressibility of individual layers. The pressure dependence of the volume by linearizing the Birch–Murnaghan equation of state as a function of Eulerian strain shows a clear change of the bulk modulus at the ETT pressure of ∼20 GPa. The minimum of c / a ratio around 32 GPa is associated with the change in topology of electron pockets marked as second ETT of Lifshitz-type. We do not observe any structural transition up to the maximum applied pressure of ∼46 GPa under quasi-hydrostatic condition.